Role of vitamin K-dependent proteins in the arterial vessel wall - Chatrou, M. L. L.; Reutelingsperger, C. P.; Schurgers, L. J. (Hämostaseologie, 2011)
Vitamin K was discovered early last century at the same time as the vitamin K-antagonists. For many years the role of vitamin K was solely ascribed to coagulation and coagulation was thought to be involved only at the venous blood side. This view has dramatically changed with the discovery of vitamin K-dependent proteins outside the coagulation cascade and the role of coagulation factors at the arterial side. Vitamin K-dependent proteins are involved in the regulation of vascular smooth muscle cell migration, apoptosis, and calcification. Vascular calcification has become an important independent predictor of cardiovascular disease. Vitamin K-antagonists induce inactivity of inhibitors of vascular calcification, leading to accelerated calcification. The involvement of vitamin K-dependent proteins such as MGP in vascular calcification make that calcification is amendable for intervention with high intake of vitamin K. This review focuses on the effect of vitamin K-dependent proteins in vascular disease.
Keywords: Vitamin K; vitamin K-antagonists; MGP; vascular calcification